Marketing strategies in the internationalization process of Brazilian franchises - Camargo, Maria Adriana de A. P.; Rocha, Thelma Valéria; Silva, Susana Costa e (Review of Business Management, 2016)
Purpose – This paper aimed to analyze the influence of marketing strategies on the internationalization process of Brazilian franchises. The objective was to identify the marketing strategies used by Brazilian franchises during different stages of their internationalization processes and to analyze these strategies according to the Global Marketing Strategy (GMS). Design/methodology/approach – The paper adopted a qualitative research methodology based on three case studies developed in Brazilian franchises in the footwear and apparel sector: two companies with active involvement and one with commitment involvement abroad. Six directors and marketing managers of these companies provided statements regarding the internationalization process and marketing strategies. Findings – The Brazilian franchises are on the path towards standardizing their marketing mix, but they are still a long way from leading their business actions to the four final dimensions of the GMS: concentration and coordination of marketing activities, integration of competitive movements and participation in the global market. Secondly, we performed a comparative analysis of the three case studies considering active and commitment involvement. Originality/value – This study innovates using the GMS to analyze the internationalization processes of Brazilian franchises in different stages, and it emphasizes the dimensions that should be subjects of planning for firms that are preparing to grow their franchising business models abroad.